Forecasting denosumab - Calkins, Tim; Aggarwal, Nayna ([London] : SAGE, 2016)
This case looks at an important business task: forecasting a new product. The case can be used to teach finance, marketing (new product introduction), and healthcare strategy. The product is one of Amgen's most important new products: denosumab. On the surface, the case is fairly easy; students simply have to do some simple mathematical calculations. However, the challenges of forecasting quickly become apparent; every forecast depends on some critical assumptions, and the answer can vary dramatically.
Originally Published in: Calkins, T. & Aggarwal, N. (2011). Forecasting denosumab. 5-111-004. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; New products -- Management -- Case studies; New products -- Marketing -- Case studies; New business enterprises -- Case studies; Business forecasting -- Case studies